Narrowing the set of complex systems' possible design solutions derived from the set-based concurrent engineering approach. (September 2019) - Ammar, Randa; Hammadi, Moncef; Choley, Jean-Yves; Barkallah, Maher; Louati, Jamel; Haddar, Mohamed
Nowadays, complex systems are dominating our contemporary as well as professional lives. These modern technical products are considered as mechatronic systems which incorporate mechanics with electronics, software, and control in various domains mainly transport, medicine, and robotics. The development of these modern technical products is thus so tough. Hence, mechatronics' critical challenges are to be not only well understood but also supported by practical models and tools in order to overcome this difficulty. Moreover, using the traditional design method which is point based is inefficient as it leads to a huge decrease in the innovation potential through limiting the design space to few solutions, an important increase in the cost of the product as well as production delay due to the great number of iterations. Some product development practices have shifted from using the "fixed-point design" approach to the "set-based design" one. Indeed, the set-based concurrent engineering widely considers a set of possible solutions and then shrinks the number of possibilities in order to converge toward a final solution. Yet, since this approach is too difficult to be put into action, a small number of industries in the field of mechatronics use the set-based concurrent engineering concept. Accordingly, this work aims to develop a novel method for the purpose of facilitating the development of a complex product based on the set-based concurrent engineering method and its implementation in an industrial setting by developing an algorithm to find the set of possible solutions to the design problem and narrow this set to merge toward the final solution. Finally, this algorithm is implemented using "Python" language.